STUDI PERHITUNGAN SUMBERDAYA BATUBARA PADA LAPISAN HANGING SEAM DAN SEAM UTAMA DENGAN METODE CIRCULAR DI DAERAH TOWNSITE DAN SEKITARNYA, TANJUNG ENIM, SUMATERA SELATAN - Tambaria, Theodora Noely (Geological Engineering E-Journal, 2013)
South Sumatra Basin consists of a variety of rock formations and there is a wide range of natural resources that can be developed, either at Muara Enim formation. At Muara Enim formations are sandstone and limestone unit with inset coal. Mapping based on Townsite and surrounding area, Tanjung Enim generally known in claystone unit obtained layers are less thick hanging seam, with a transitional sedimentary structures that characterize the upper delta plain leads more towards land. Whereas the tuff sandstone unit generally obtained main seam layer is thick enough to sedimentary structures that characterize the transitional upper delta plain leads more towards the sea. Coal resources used in the calculation method for calculation with circular because the circular method is to make the area of influence of the observation point, and then calculated the extent of influence of each region with coal limit and the work sheet area, the extent of each area multiplied by the thickness of the average seam being calculated, and multiplied by the density is in accordance with local circumstances which are still at the stage of preliminary exploration. Resource calculation performed on Townsite and surrounding area, Tanjung Enim with circular method known coal seam is hanging reserve 27,950,679.6 tons , while coal reserves are the main seam 129724447.5 tons. Based on the calculations have been made known to the main seam to be mined is more economical compared to hanging seam, but for the addition of hanging seam coal resources can be considered.